Where Does Art Come From? - McCurdy, Leah (Open textbook library., 2022)
Who am I? What is beautiful? Where do babies come from? These questions populate our lives and inform our perceptions of the world. Explore these questions according to the expressions of artists from all over the world. Go beyond Western art to consider where art comes from and how it impacts all of us.